The effect of disaster management education on citizen preparedness facing floods - Pabio, Pabio Leo capilo; Novikasari, Linawati; Winarno, Rudi; Trismiyana, Eka (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Natural disasters, especially floods, have become a crucial issue in Indonesia. Indonesia's geographical position as an archipelagic country that crosses the equator makes it vulnerable to high rainfall, which often triggers hydrometeorological disasters such as floods. Purpose: To determine the influence of health education about flood first aid on the mental readiness of the community in facing disasters. Method: A quantitative design with a quasi-experimental approach type one group pre-test post-test design. The research sample consisted of 30 respondents selected from 85 heads of families in RT 03 Nyunyai Village. Data was collected using a validated questionnaire. Data analysis included univariate analysis, normality test with Kolmogorov-Smirnov, and bivariate analysis with t-test. Results: A significant increase in knowledge and skills after being given health education interventions. The average score of knowledge and skills increased from 11.60 on the pre-test to 15.47 on the post-test. The results of the t-test proved a significant influence with a p-value of 0.000 (< 0.05). Conclusion: Health education has a significant influence in increasing the knowledge and preparedness of the people of Nyunyai Village regarding first aid during floods. Keywords: Communities; First Aid; Floods; Health Education; Preparedness.